Impact of bias field correction on 0.35 T pelvic MR images: evaluation on generative adversarial network-based OARs’ auto-segmentation and visual grading assessment - Vagni, Marica; Tran, Huong Elena; Catucci, Francesco; Chiloiro, Giuditta; D’Aviero, Andrea; Re, Alessia; Romano, Angela; Boldrini, Luca; Kawula, Maria; Lombardo, Elia; Kurz, Christopher; Landry, Guillaume; et al. (Frontiers in Oncology, 2024)
Purpose: Magnetic Resonance Imaging (MRI)-guided Radiotherapy enables adaptive treatment plans based on daily anatomical changes and accurate organ visualization. However, the bias field artifact can compromise image quality, affecting diagnostic accuracy and quantitative analyses. This study aims to assess the impact of bias field correction on 0.35 T pelvis MRIs by evaluating clinical anatomy visualization and Generative Adversarial Network (GAN) auto-segmentation performance.Materials and methods: 3D simulation MRIs from 60 prostate cancer patients treated on MR-Linac (0.35 T) were collected and pre-processed with the N4ITK algorithm for bias field correction. A 3D GAN architecture was trained, validated and tested on 40, 10 and 10 patients, respectively, to autosegment the Organs At Risk (OARs) rectum and bladder. The GAN was trained and evaluated either with the original or the bias-corrected MRIs. The Dice similarity coefficient (DSC) and 95 th percentile Hausdorff distance (HD95 th ) were computed for the segmented volumes of each patient. The Wilcoxon signed-rank test assessed the statistical difference of the metrics within OARs, both with and without bias field correction. Five radiation oncologists blindly scored 22 randomly chosen patients in terms of overall image quality and boundaries visibility (prostate, rectum, bladder, seminal vesicles) of the original and bias-corrected MRIs. The Bennett's S score and the Fleiss' kappa were used to assess the pairwise inter-rater agreement and the inter-rater agreement among all the observers, respectively.In the test set, the GAN trained and evaluated on original and bias-corrected MRIs showed DSC/HD95 th of 0.92/5.63mm and 0.92/5.91mm for the bladder, and 0.84/10.61mm and 0.83/9.71mm for the rectum. No statistical differences in the distribution of the evaluation metrics were found neither for the bladder (DSC: p=0.07; HD95 th : p=0.35), nor for the rectum (DSC: p=0.32; HD95 th : p=0.63).From the clinical Visual Grading Assessment, the bias-corrected MRI resulted mostly in either no change or an improvement of the image quality and organs boundaries' visualization, compared to the original MRI.The bias field correction did not improve the anatomy visualization from a clinical point of view, nor the OARs auto-segmentation outputs generated by the GAN.